The Influence of Perceived Usefulness, Social Influence, and User Experience on Technology Acceptance Intention in Startup Companies - Tawil, Muhamad Risal; Darwis, Darwis; Pahlawansah, Haniwijaya; Violin, Vivid; Astuti, Enny Diah; Lubis, Fatimah Malini (Yayasan Gema Bina Nusantara, 2025)
This​‍​‌‍​‍‌ study is centered around the idea of how the factors like perceived usefulness, social influence, and user experience impact the employee's intention to technology acceptance in the startups of Indonesia. The study was performed by us through a quantitative approach and a questionnaire of 150 employees from different digital startups in Indonesia. I ensured that the participants met the criteria of being technology users in their daily work. The data analysis was done through multiple linear regression. The results of the research show that the three factors, i.e. perceived usefulness, social influence, and user experience, have positive and significant impacts on the technology acceptance ​‍​‌‍​‍‌intention. Perceived usefulness focuses on the benefits of technology and increases confidence, social influence enhances positive social norms, and user experience offers a more comfortable and intuitive digital encounter. Theoretically, this study adds to the knowledge of Technology Acceptance Model (TAM) in the context of startups, and practically, I aim to provide management with the recommended approach to bolster digitalization efforts using perceived usefulness, social support, and user experience in the strategy.